Down-regulation of the large conductance Ca2+-activated K+ channel expression in C57BL/6J cochlea. (1st September 2016) - Pan, Chunchen; Chu, Hanqi; Lai, Yanbing; Liu, Yun; Sun, Yanbo; Du, Zhihui; Chen, Jin; Tong, Ting; Chen, Qingguo; Zhou, Liangqiang; Bing, Dan; Tao, Yanling
Abstract: Conclusion : The large conductance Ca 2+ -activated K + channels (BK) expression is decreased in the cochleae of age-related hearing loss (AHL) mice. BK channel may be associated with AHL. Objective : AHL is the most common among elderly persons. BK channels act as sensors for membrane voltage and intracellular Ca 2+ and are essential for hearing. To investigate the distribution of BK channel in the cochleae of C57BL/6J mice, and the relationship between the expression of BK channel and the etiology of AHL. Methods : BK expression was studied in the cochleae of C57BL/6J mice at various ages (4, 12, 26, 52 weeks). The expressions of BK at the protein and mRNA levels were detected by immunofluorescence technique, western blot and quantitative real time PCR. Results : In comparison with 4-week-old mice, BK expressions in the cochleae at 12, 26 and 52 weeks of age were significantly and gradually decreased at both the protein and the mRNA levels. The immunofluorescence technique showed the BK channel was located in the hair cells and cells of the spiral ganglion, spiral ligament and stria vascularis and its expression also decreased with aging.